Usefulness of fecal calprotectin for the early prediction of short-term outcomes of remission-induction treatments in ulcerative colitis in comparison with two-item patient-reported outcome - Toyonaga, Takahiko (PLoS One, 2017)
BACKGROUND: Fecal calprotectin (FC) is well accepted as a non-invasive biomarker which objectively reflects colonic inflammation in ulcerative colitis (UC). However, its value as a marker of response during the early phase of remission induction treatment has not been well studied. The aim of this study is to evaluate the significance of FC for predicting the short-term outcomes of remission induction treatment in patients with UC. METHODS: A prospective observational study was conducted among 31 patients with active UC. FC was monitored with two-item patient-reported outcome (PRO2), partial Mayo score (PMS), and Lichtiger clinical activity index (CAI) during the first 4 weeks of remission induction treatment. Clinical response was defined as a decrease in CAI of 3 or more points below baseline. Mucosal healing (MH) was defined as Mayo endoscopic subscore 0 or 1. Within-day and within-stool variability of FC were assessed during the first week of treatment. RESULTS: In week 4-clinical responders, PRO2, PMS, and CAI significantly decreased from day 3, however, FC did not show significant reduction until week 2. Among all markers, the decrease in PRO2 at week 4 most accurately predicted MH at week 12. Within-day variability of FC was remarkably wide even at the first week in clinical responders. Within-stool variability was extremely small. CONCLUSIONS: PRO2 predicted the short-term outcomes of remission induction treatment earlier than FC possibly because of the wide within-day variability of FC in active UC.